Star wars book 2 : the lost city of the Jedi - Davids, Paul.; Davids, Hollace; Kesel, Karl (New York : Batnam Books, 1992)
Having gained possession of the glove of Darth Vader, the evil Trioculus seeks to destroy the Jedi Prince who will be a threat to his reign.
Keywords: Fiction